Climate change and vulnerability discourse by students at a South African university - Shingirai S. Mugambiwa; Obey Dzomonda (Jàmbá, 2018)
Climate change is expected to pose grave consequences to communities around the world. It is predicted that many people, mostly in the developing world, will experience shortages of water and food as well as numerous health-related effects because of climate change. Therefore, rigorous global action is needed to enable developing countries to adapt to the effects of climate change. Universities play a pivotal role in addressing these issues and their impacts through research and technological innovations. Hence, assessing the extent to which university students understand climate change and its impacts displays the extent of hope in mitigating future changes in climatic conditions. This article assesses the knowledge and understanding of climate change and its impacts by students at an institution of higher learning in South Africa. This study utilised a quantitative approach and a descriptive design. The convenience method was used to obtain participants for the study. Self-administered questionnaires were utilised in a survey to collect data from the participants. A sample of 90 university students participated in the survey. Data analysis included descriptive statistics and T-tests. Reliability was measured using the Cronbach’s alpha. The study discovered that university students have low knowledge and understanding of climate change. As a result, the study concluded that if students could be well-informed about climate change issues, they could positively contribute to the development of their communities by crafting smart climate change mitigation and adaptation skills.